Signals from both sides: Control of cardiac development by the endocardium and epicardium - Smith, Travis K. (2006)
It is readily apparent that the process of heart development is an intricate one, in which cells derived from many embryonic sources coalesce and coordinate their behaviors and development, resulting in the mature heart. The behaviors and mechanisms of this process are complex, and still incompletely understood. However, it is readily apparent that communication between diverse cell types must be involved in this process. The signaling that emanates from epicardial and endocardial sources is the focus of this review.